The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.rli.0000113776.87762.49
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxicity of Iodinated Radiocontrast Agents on Renal Cells In Vitro

Abstract: A deterioration of renal function is one preoccupying complication of iodinated radiocontrast agents in clinical practice. These compounds have direct toxic effects on renal cells, which are only in part related to their physicochemical properties. The hyperosmolal monomeric ionic radiocontrast agents, like diatrizoate, have the highest toxicity, whereas renal cells are less affected by (nonionic) compounds with reduced osmolality. The toxic effects include cellular energy failure, a disruption of calcium home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(133 citation statements)
references
References 51 publications
2
125
0
6
Order By: Relevance
“…Exposure periods of several hours are required to induce toxicity in NRK 52-E cells, and this is consistent with the findings of others. 8 This prolonged exposure is relevant to the clinical setting as renal retention of low doses of ICM in the kidney has been reported for up to 32 h after administration of ICM. 20 The concentration of the ICM used in the current study was selected on the basis of previously reported in vitro …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exposure periods of several hours are required to induce toxicity in NRK 52-E cells, and this is consistent with the findings of others. 8 This prolonged exposure is relevant to the clinical setting as renal retention of low doses of ICM in the kidney has been reported for up to 32 h after administration of ICM. 20 The concentration of the ICM used in the current study was selected on the basis of previously reported in vitro …”
Section: Discussionmentioning
confidence: 99%
“…6 In vitro studies support the hypothesis that the toxicity is related to the osmolality of the ICM, as low-osmolal ICM (LOCM) have considerably less toxic effects than high-osmolal ICM (HOCM) on various cell types, with the observed toxicity being dose dependent. 8,9 The ionic force of the molecule seems to be irrelevant to the toxicity. 8 However, other studies have shown that mannitol, when tested at equal osmolality to the contrast media, induced less toxicity than ICM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, small iodinated molecules are routinely used for in vivo contrast enhancement in the clinical setting, since iodine has a high X-ray absorption coefficient among nonmetal atoms. However, short circulation half-life, non-specific distribution, and potential renal toxicity have limited their imaging and targeting performance in vivo [129]. Liposomes with entrapped iodinated molecules are effective contrast agents due to their prolonged circulation half-time [130].…”
Section: Nanoparticle-based Mri and Mr/pet Imaging Contrast Agentsmentioning
confidence: 99%